Peran Pusat Kegiatan Belajar Masyarakat (PKBM) Darul Hikam Dalam Mengembangkan Keterampilan Masyarakat di Desa Sukakerta Kecamatan Cilamaya Wetan - Muhamad Nuzlan Fadhlillah; Sutarjo Sutarjo; Abdul Muis (Peneliti.net, 2022)
The competitive demands of the world of work require quality human resources. The policy strategy issued by the government in order to improve the quality of human resources is through the skills and abilities of students. The Center for Community Learning Activities (PKBM) is one aspect of the government's policy strategy in improving human resources. The purpose of the topic of this discussion is to find out whether the PKBM where the research has an impact on the local community so that it is able to increase its own resources through the skills aspect. The importance of this discussion topic being used as research is that it can be used as a reference source for similar institutions to provide an overview of the achievements obtained from the process that is being carried out. The type of approach used in this research is qualitative using the case study method. The data were obtained from the number of respondents as many as 10 people consisting of managers, tutors and learning residents. Furthermore, the results of research conducted through interviews, observations and documentation as data collection techniques showed that the success of the community in developing their skills as an increase in human resources was the fruit of the big role given by PKBM to learning citizens. Moreover, people's lives are much better since the establishment of these non-formal institutions. The importance of the results of this research will have a positive impact on the institution that is the subject of research as well as existing similar institutions